Sistem Pencarian Informasi Berbasis Ontologi untuk Jalur Pendakian Gunung Menggunakan Query Bahasa Alami dengan Penyajian Peta Interaktif - Fadhila Tangguh Admojo; Edi Winarko (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
Mountain climbing path information has been widely available on the internet. However, to get information that suits the needs of climbers take time to browse and compare all the available information. The diversity of the search results content actually confuse the climbers. This research aims to provide a solution to the problems faced by climbers, by developing an information retrieval system for mountain climbing path using semantic technology (ontology) based approach . The system is developed by using two knowledge base (ontology), ontology Bahasa represents linguistic knowledge and ontology Mountaineering represents mountaineering knowledge. The system is designed to process and understand natural language input form. The process of understanding the natural language based on syntactic and semantic analysis using the rules of Indonesian grammar. The results of the research that has been conducted shows that the system is able to understand natural language input and is capable of detecting input that is not in accordance with the rules of Indonesian grammar both syntactically and semantically. The system is also able to use a thesaurus of words in the search process. Quantitative test results show that the system is able to understand 69% of inputs are taken at random from the respondents.